Socialization of the Use of Geogebra Learning Media in Mathematics Subjects to Increase Student Creativity - Rini, Zulmi Roestika; Rizqi, Hesti Yunitiara; Wibisono, Iwan Setiawan (Fakultas Komputer dan Pendidikan Universitas Ngudi Waluyo, 2023)
Community service activities can be seen from the analysis of teacher needs in learning that can instill the creative thingking of elementary school students by using the Geogebra Media. The use of Geogebra on students can improve their skills and get better results. Activities carried out at SDN Jubelan 01 use the community development method which functions of preparation, introduction, socialization, training on the use of Geogebra and compiling creative thingking assessments, monitoring, and evaluation. The results of this activity that students' creative characters have been embedded by using Geogebra obtained an average of 85.08% very good category with an indicator of 91.20% of students trying new ways to resolve a problem, 94.30% of students using various media/sources to solve a problem, 83.30% of students ask about related material to get their ideas or ideas, 77.50% of students have a problem solving that is different from others, and 79.10% of students have many ideas and suggestions for a problem.. Therefore, the results of service activities in using Android-based Geogebra provide a visual experience for students to understand geometry material so that they can instill students' creative thingking in elementary schools.